Avena sativa AV25-T (Altoandina) supplementation as alternative for Colombia's high-altitude dairy systems: An economic analysis - Enciso, Karen; Castillo, Javier; Albarracín, Luis; Campuzano, L; Sotelo Cabrera, Mauricio Efren; Burkart, Stefan (Frontiers Media, 2021)
In the Colombian high-altitude tropics (2,200–3,000 m.a.s.l.), Kikuyu grass (Cenchrus clandestinus) is the main feed source for the dairy system. This grass species has good characteristics regarding adaptability and productivity, but is affected by frost, grass bugs (Collaria spp.) and precipitation-related production seasonality. Forage deficits might thus be a problem at several times in a year. As a strategy to maintain production stable, dairy farmers use commercial feed concentrates increasing their production costs. Agrosavia, as a response to this, started in 2005 with the evaluation and selection of new forage species for the Colombian high-altitude tropics. The oat Avena sativa AV25-T was identified as promising alternative to supply the requirements of dry matter in times of deficit and released as cultivar in 2018 under the name Altoandina. The objective of this study was to evaluate the economic viability of Altoandina in Colombia's high-altitude dairy systems. Altoandina (Aa) was provided as silage in two different diets: 35%Aa−65% Kikuyu (Yellow Diet) and 65%Aa-35% Kikuyu (Red Diet). The diet for comparison was traditional grazing with 100% Kikuyu grass (Blue Diet). All diets were supplemented with 6kg commercial feed concentrate, 0.5 kg cotton seeds and 0.5 kg Alfalfa meal per cow/day, respectively. To estimate economic indicators, we used a cashflow model and risk assessment under a Monte Carlo simulation model. Including Altoandina incremented productivity per hectare by 82.3 and 220% in the Yellow and Red Diets, respectively. According to the results of our economic model, the Yellow Diet is the best alternative. Its average Net Present Value (NPV) was superior in >80% and showed a lower variability. The indicators Value at Risk (VaR) and probability (NPV < 0) show the Yellow Diet to have the lowest risk for economic loss under different yield/market scenarios. The Yellow Diet also has the lowest unit production costs and uncertainty of productive parameters. According to our findings, supplementation with Altoandina at 35%, i.e., during critical times, has high potential to improve efficiency and profitability. This information is key for the decision-making process of dairy farmers on whether to adopt this technology.